Vascular Tissue Analysis as a Decisive Tool for Tropical Hardwood Identification: The Case Study of Ekop Species in Cameroon - Pierre Paul Mbarga; Armand William Mala; Marie Marguerite Mbolo (International Journal of Forestry Research)
The perforation plates and vessel-ray pitting of tropical hardwoods are typical features that make it possible to mark species within a botanical family. This study aims to bring out a consistent and robust framework for a clear distinction through anatomical features among various Ekop woods based on usual nomenclature on trade. Perforations plates and vessel-ray pitting are determining components for the classification of the species. Indeed, several species exploited under the trade name Ekop because of their grain, color, and wooden decoration patterns do not belong to the same taxonomic class. With the natural structure of cells and their intervessel pits observed in xylem and phloem, it appears that the perforation plates and the vessel-ray pitting are decisive components for the classification of Ekop species. Forty-three wood specimens of Ekop were collected from forests in Ebolowa, Mbalmayo, and Abong Mbang. In addition, 155 microscopic sections of Ekop slides with at least 3 representatives of identified species were observed. Thus, macroscopic observations through a hand magnifying glass were performed on wood carrots. Then, the microscopic sections of slides in the first 63 features of the International Association of Wood Anatomists list were analyzed. Correlations were observed between vessels elements and other main features through component analysis. Four groups of Ekop were differentiated by gathering in each genus a matrix of similar features across their vessels groupings, perforation plates, and vessel-ray pittings. A tabular key was used to further define the identity of the Ekop species. This study makes it possible to recognize Ekop wood beyond the dendrological aspects of vegetative and reproductive organs. Finally, a few typical features used for a precise demarcation were identified, for a taxonomic classification within the Ekop group.